Correlation of auditory 'oddball' P300 with verbal memory deficits in schizophrenia. - Shajahan, P; O'Carroll, R; Glabus, M; Ebmeier, K; Blackwood, D (1997)
BACKGROUND: The study attempts to recruit well known 'cognitive' event related potential measures as an objective estimate of cognitive and specific memory impairment in schizophrenia. METHODS: We examined 19 schizophrenic patients and 28 healthy controls using an auditory discrimination task to elicit event related potentials, and a number of neuropsychological tests, including tests of general intellectual ability, putative frontal lobe function and verbal memory. RESULTS: The late positive deflection presumed to be associated with stimulus evaluation (P300) was of lower amplitude and had a longer latency in the patients compared with controls of similar age and sex. We found correlations between P300 amplitude and latency, and neuropsychological performance scores in patients. There were correlations between decreased P300 amplitude and lower IQ and poorer memory performance, in particular, abnormal semantic clustering, discriminability and intrusion errors. Increased P300 latency was correlated with lower pre-morbid IQ, poorer total memory scores and serial clustering, but paradoxically less relative retrieval deficit and fewer intrusion errors. CONCLUSIONS: These findings suggest that abnormal P300 is generally more likely to occur in patients with memory impairment.